2020
DOI: 10.1186/s13054-020-02988-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization practices in critically ill children: a European point prevalence study (EU PARK-PICU)

Abstract: Background: Early mobilization of adults receiving intensive care improves health outcomes, yet little is known about mobilization practices in paediatric intensive care units (PICUs). We aimed to determine the prevalence of and factors associated with physical rehabilitation in PICUs across Europe. Methods: A 2-day, cross-sectional, multicentre point prevalence study was conducted in May and November 2018. The primary outcome was the prevalence of physical therapy (PT)-or occupational therapy (OT)-provided mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 34 publications
3
43
0
4
Order By: Relevance
“…Otherwise, the nurse and families are provided with written instructions for mobility activities. As a part of this initiative, nurses, other staff members, and caregivers were educated and empowered to actively participate in mobility activities, an essential aspect of early mobility in critically ill children (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the nurse and families are provided with written instructions for mobility activities. As a part of this initiative, nurses, other staff members, and caregivers were educated and empowered to actively participate in mobility activities, an essential aspect of early mobility in critically ill children (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Early mobility is a promising therapeutic option that addresses many of these issues. Although adult studies suggest clinical benefit from early mobility and rehabilitation (25)(26)(27), the use of rehabilitation resources is low in the pediatric population, with a point prevalence of 35-39% (28,29). Early mobility-based rehabilitation programs designed to increase mobilization within 72 h of ICU admission in pediatrics are reported to be both safe and feasible and to increase physical/ occupational therapy consults and early mobilization events (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…"-Florence Nightingale Many perceived barriers to EM in the PICU have been reported in different studies, at the level of patient, provider, institution and knowledge translation (34,51). Resource and time constraints and increased workload are commonly cited; safety concerns are common, with patients often perceived as being "too sick" and physiologically unstable to safely tolerate mobilization, especially early in their admission; sedation practices may limit the cooperative ability of patients; the patients themselves may lack motivation or the ability to cooperate; the presence of invasive lines, airways and devices create concern about dislodging during movement; certain medications may be associated with increased risk; and delirium may further limit patient participation (29,31,32,34,35,52,(64)(65)(66)(67). Owing to these perceptions of risk, the youngest and sickest patients tend to receive the fewest rehabilitation interventions, and likely remain at the greatest risk of PICS (67).…”
Section: Building a Picu Quality Culturementioning
confidence: 99%
“…quality improvement initiative (n=200) reported no associated adverse events with the use of a stratified early rehabilitation program (38). Similarly, recent point-prevalence (PARK-PICU) studies of mobilization practices in Europe and the USA reported only minor adverse events, most commonly transient changes in vital signs (31,32). Studies in specialized populations, for example following placement of ventricular assist devices, liver transplantation, and patients on extracorporeal membrane oxygenation (ECMO) awaiting lung transplantation have also not described serious adverse events associated with mobilization activities (45)(46)(47)(48).…”
mentioning
confidence: 94%
See 1 more Smart Citation